A self-floating electrospun nanofiber mat for continuously high-efficiency solar desalination. (October 2021) - Liang, Pingping; Liu, Shuai; Ding, Yadan; Wen, Xiaokun; Wang, Kexin; Shao, Changlu; Hong, Xia; Liu, Yichun
Abstract: Solar desalination is an environment-friendly and sustainable technology to address the shortage of freshwater resources. However, it still faces huge challenges to develop a salt-rejection solar desalination system with continuous high efficiency. Herein, an electrospun nanofiber mat was fabricated for continuously high-efficiency solar desalination with carbon nanotube as a photothermal material, polyvinylidene fluoride as a floating support material and polyvinylpyrrolidone as a pore-forming agent. The porous structure and superhydrophilic surface provide significant water transport channels and thus avoid salt deposition, even in the high-salinity brine (20 wt% NaCl). The integration of strong broadband absorption property, excellent photothermal performance, floatability, durability and stability endows the solar desalination system with continuously high evaporation efficiency. The evaporation rate and solar conversion efficiency reached up to 1.372 kg m −2 h −1 and 86.1%, respectively, in simulated seawater under one sun irradiation and lasted for 11 h with little fluctuation. This work opens a new avenue for the rational design and fabrication of solar desalination systems to promote practical application. Graphical abstract: Image 1 Highlights: A desalination system based on a CNT-PVDF-PVP nanofiber mat is fabricated. Porous structure and superhydrophilic surface facilitate to avoid salt deposition. The continuous high evaporation efficiency is achieved. The desalination system exhibits strong light absorption, floatability and stability.